Las actividades lúdicas como estrategia didáctica para el proceso de enseñanza-aprendizaje de la unidad 7: El continente americano, con estudiantes de 8vo. año de EGB. - Chiliquinga Quishpi, Brigith Estefania (2024)
The primary objective of this research is to construct recreational activities that enable an adequate teaching-learning process of Unit 7, corresponding to the American continent of the text of Social Studies of the 8th year of EGB, the feasibility of this work is supported by conceptual contributions that analyze qualitative and quantitative data from surveys of 122 students of the Educational Unit "María Inmaculada" and the teacher responsible for the subject through in-person interviews. It is important to mention that the study employs descriptive, bibliographic, and field research to identify variables that support the research but have not been manipulated; as a result of the play activities, we have been able to appreciate the development of social, reflective, and creative skills, which promoted interest, participation, and collaborative work in the classroom.